Implementasi Si Cerdas Bu Priska pada Kantor Dinas Kependudukan dan Pencatatan Sipil terhadap Kepuasan Masyarakat Kabupaten Gowa - A. Noerhayati Amirullah (Journal of Management and Social Sciences, 2025)
This research aims to analyze the implementation of the BU PRISKA CERDAS Information System (SI) at the Gowa Regency Population and Civil Registration Service Office and its impact on community satisfaction. The method used is quantitative descriptive, with data collection through interviews, observation and documentation. The type of research used in this research is quantitative descriptive. This type of descriptive research is analysis that is explanatory or elaborate on the data and information obtained, then linked to relevant theories or concepts to provide a real picture or actual facts, so that conclusions can be drawn. The results of the research show that services through SI CERDAS BU PRISKA have a positive effect on community satisfaction, with high indicators of satisfaction in service procedures, speed and infrastructure. SI CERDAS BU PRISKA online services have an influence on community satisfaction at the Gowa Regency Population and Civil Registration Office. . This can be seen from the results of interviews with residents in the highlands and lowlands of Gowa Regency. SI CERDAS BU PRISKA online service procedures run according to applicable standards, it can be seen that the people of Gowa Regency are very satisfied with SI CERDAS BU PRISKA services compared to manual population administration services at the office.